2007
DOI: 10.1007/s11605-007-0290-0
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Perioperative Dexmedetomidine Infusion on Postoperative Narcotic Use and Duration of Stay after Laparoscopic Bariatric Surgery

Abstract: Dexmedetomidine (Precedex, Hospira, Lake Forest, IL) is an alpha-2 receptor agonist with sedative and analgesic sparing properties. This medication has not been associated with respiratory suppression, despite occasionally high levels of sedation. For 10 months, all patients undergoing a laparoscopic bariatric procedure received a dexmedetomidine infusion 30 min before the anticipated completion of the procedure (n = 34). A control group was comprised of a similar number of patients to have had laparoscopic ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 15 publications
1
26
0
2
Order By: Relevance
“…Although dexmedetomidine is commonly used as an adjunct anesthetic in bariatric surgery, no previous studies have assessed dexmedetomidine pharmacokinetic profile in the obese population. Dexmedetomidine loading doses and infusion rates are currently calculated on a milligram per kilogram (mcg/kg) TBW basis in both nonobese and obese patients [10].…”
Section: Introductionmentioning
confidence: 99%
“…Although dexmedetomidine is commonly used as an adjunct anesthetic in bariatric surgery, no previous studies have assessed dexmedetomidine pharmacokinetic profile in the obese population. Dexmedetomidine loading doses and infusion rates are currently calculated on a milligram per kilogram (mcg/kg) TBW basis in both nonobese and obese patients [10].…”
Section: Introductionmentioning
confidence: 99%
“…Th e patient with compromised pulmonary function may be at an increased risk for an adverse event. Dexmedetomidine, an alpha 2-adrenoceptor agonist, has been used to provide sedation in critical care patients and has been demonstrated to reduce opioid requirements, cause minimal respiratory depression, and improve outcomes (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). We hypothesized that the addition of a dexmedetomidine infusion to the postoperative pain management protocol would reduce the amount of morphine delivered by a PCA pump, reduce the opioid-induced adverse drug eff ects, and provide adequate analgesia for postthoracotomy patients.…”
mentioning
confidence: 99%
“…One retrospective 16 study and two prospective, randomized controlled trials [17][18][19] in bariatric surgical patients have found that a balanced anaesthetic with desflurane or propofol plus dexmedetomidine reduces postoperative morphine consumption, and improves haemodynamics compared with desfluranefentanyl or propofol-fentanyl anesthetics. In our study, we have used morphine for analgesia in both groups but the requirement of additional dose of morphine was decreased in patients who received dexmedetomidine compared to those who received saline.…”
Section: Discussionmentioning
confidence: 99%